Socioeconomic Factors Associated With the Use of Telehealth in Primary Care Services During the COVID-19 Pandemic - Carlota Quintal; Aida I. Tavares; Inês Ribeiro; Victor Raposo; Pedro L. Ferreira (Journal of Primary Care & Community Health, 2025)
Introduction: The main objective of this study was to assess whether socioeconomic factors were associated with the use of telehealth in primary care services in Portugal during the COVID-19. Methods: A questionnaire was administered to patients in primary healthcare units during the pandemic. The set of variables used in this study was part of a larger patient satisfaction questionnaire. A descriptive statistical analysis was performed, and a multiple logistic regression analysis was estimated to assess factors associated with using remote consultation. Results The use of a remote consultation was reported by 38.2% of respondents (N = 7008), and the main reason for telehealth use was prescription renewal. Among non-users of telehealth, 40% did not know they could contact their family doctor by email. Factors positively associated with telehealth use were: older age, women, married, filled questionnaire without help, consumption of OTC and prescribed drugs, unmet healthcare needs, and registered with family doctor. The evidence suggests a negative association between education and telehealth use. Conclusions: No clear pattern emerged regarding the digital divide. The evidence shows a relevant lack of awareness regarding the possibility of using telehealth. If more complex forms of telehealth are adopted in primary care services, the digital divide might come to the surface.